2019
DOI: 10.1177/2058739219838396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of norepinephrine on hemodynamics, vascular elasticity, cardiac pump function, and inflammatory factors in patients with septic shock

Abstract: The effects of norepinephrine on hemodynamics, vascular elasticity, cardiac pump function, and inflammatory factors in patients with septic shock remained unknown. In this study, we included 124 cases of severe septic shock patients in our hospital. The patients were randomly divided into control group (treated with dopamine) and experimental group (treated with dopamine plus norepinephrine), while the hemodynamic index (heart rate (HR)), blood vessel elasticity index, heart pump function, and inflammatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…1). Similar to previous study [10], presumably, increasing NE could convert unstressed volume into stressed volume and causes increasing of VR and cardiac preload as previously mentioned in several studies [10,[25][26][27][28]. However, we found no signi cant difference in Ea/Ees compared between baseline-1 and post-NE while previous study found that NE worsen VA coupling [10].…”
Section: Discussionsupporting
confidence: 90%
“…1). Similar to previous study [10], presumably, increasing NE could convert unstressed volume into stressed volume and causes increasing of VR and cardiac preload as previously mentioned in several studies [10,[25][26][27][28]. However, we found no signi cant difference in Ea/Ees compared between baseline-1 and post-NE while previous study found that NE worsen VA coupling [10].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we found changing CO also correlated with changing Pvr (Figure 6). Similar to a related study [10], presumably, increasing NE could convert unstressed volume into stressed volume and increasing VR and cardiac preload as mentioned in several studies [10,[25][26][27][28]. However, we found no significant difference in Ea/Ees compared between baseline-1 and postNE while one related study found that NE worsened VA coupling [10].…”
Section: Discussionsupporting
confidence: 87%
“…The remaining 12 full-text articles were assessed for eligibility, of which 4 articles were further excluded. The remaining 8 RCTs [19,[23][24][25][26][27][28][29] were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Orbegozo Cortes et al [29] and Morelli et al [28] reported the same clinical trial but with different follow-up times. The 7 included 8 RCTs [19,23,24,[26][27][28][29] involving septic shock. Wang et al [25] reported the effect of esmolol and milrinone on patients with severe sepsis, who were randomly divided into control, milrinone, and milrinone-esmolol groups.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation